2017
DOI: 10.5812/hepatmon.45929
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness Campaign and Knowledge of Iranian (Bio)Medical Students Regarding Hepatitis B and C Infections

Abstract: Background: New treatment and vaccination strategies provide the opportunity for eliminating viral hepatitis. Lack of adequate knowledge seems to be a barrier against hepatitis elimination due to the emergence of newly infected cases. Objectives: The aim of this study was to evaluate the knowledge of Iranian (bio)medical students regarding hepatitis B virus (HBV) and hepatitis C virus (HCV) infections and to determine the effect of hepatitis public awareness campaign (PAC), held by the students, on their knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Previous studies from Iran mainly focused on the knowledge and awareness of students about HBV, HCV, and HIV/ AIDS. [17][18][19][20][21][22][23][24][25] . However, in this study, we evaluated the beliefs and attitudes of college students concerning all these preventable diseases together and we had this opportunity to compare the level of awareness among three fields of study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from Iran mainly focused on the knowledge and awareness of students about HBV, HCV, and HIV/ AIDS. [17][18][19][20][21][22][23][24][25] . However, in this study, we evaluated the beliefs and attitudes of college students concerning all these preventable diseases together and we had this opportunity to compare the level of awareness among three fields of study.…”
Section: Discussionmentioning
confidence: 99%
“…23,26,27 In addition, our result was similar to Mansour-Ghanaei's, Ghahramani's, and Karimi-Sari's investigations among Iranian students. 17,18,21,23 . The results, we presented here clearly and the results of previous studies, revealed a significant lack of widespread education for HCV compared with HIV and HBV in Iranian society.…”
Section: Discussionmentioning
confidence: 99%
“…17 An intervention is needed to increase awareness regarding HBV and HCV infections, especially in high-risk groups. 14,18 We need to evaluate the current status before starting educational interventions.…”
Section: Discussionmentioning
confidence: 99%
“…To better control the spread of this pandemic, or address issues pertaining to its spread and effect on people, multidisciplinary health care team members and students are expected to collaborate fully. This in turn contributes to the recovery and minimization of the pandemic severe consequences (5)(6)(7)(8)(9). Health science students can play a valuable role in health promotion due the nature of the work they do now, as well as their more critical role as future health care providers.…”
Section: Introductionmentioning
confidence: 99%